Respuesta :
in y=a(x-h)^2+k
vertex=(h,k)
f(x)=x^2,
the vertex is (0,0)
it opens up
g(x)=(x-3)^2+9
vertex is (3,9)
opens up
vertex=(h,k)
f(x)=x^2,
the vertex is (0,0)
it opens up
g(x)=(x-3)^2+9
vertex is (3,9)
opens up
we have
[tex]g(x)=(x-3)^{2}+9[/tex]
This is the equation of a vertical parabola with vertex at point [tex](3,9)[/tex]
The parabola open upward------> the vertex is a minimum
[tex]f(x)=x^{2}[/tex]
This is the equation of a vertical parabola with vertex at point [tex](0,0)[/tex]
The parabola open upward------> the vertex is a minimum
so
the rule of the translation is
[tex]f(x)------> g(x)[/tex]
[tex](x,y)-----> (x+3,y+9)[/tex]
that means
the translation is [tex]3[/tex] units to the right and [tex]9[/tex] units up
the graph of the function g(x) is the translated graphic of the function f(x) [tex]3[/tex] units to the right and [tex]9[/tex] units up
therefore
the answer is
g(x) is shifted [tex]3[/tex] units right and [tex]9[/tex] units up